2010
DOI: 10.1002/hbm.21144
|View full text |Cite
|
Sign up to set email alerts
|

Face recognition under ambiguous visual stimulation: fMRI correlates of “encoding styles”

Abstract: Object categorization during ambiguous sensory stimulation generally depends on the activity of extrastriate sensory areas as well as top-down information. Both reflect internal representations of prototypical object knowledge against which incoming sensory information is compared. However, besides these general mechanisms, individuals might differ in their readiness to impose internal representations onto incoming ambiguous information. These individual differences might be based on what was referred to as "S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Theories of schema processing construe schema activation as a two-step process: (i) reinstatement of a generalized, abstracted knowledge template containing variables, such as action scripts or contextual factors, and their interrelations, and (ii) specific instantiations of a schema that contextualize schema variables in the current environment (Gilboa & Marlatte, 2017;Gilboa & Moscovitch, 2017;Barsalou, 1985;Thorndyke & Yekovich, 1980). Neurocognitive models suggest that (i) cross-regional communication between the vMPFC and posterior cortical areas mediate these processes, (ii) they influence how we process information in the environment, (iii) their influence is rapid, and (iv) their activation and maintenance is context-sensitive (Gilboa & Moscovitch, 2017;Fruhholz, Godde, Lewicki, Herzmann, & Herrmann, 2011;Hanson, Hanson, Halchenko, Matsuka, & Zaimi, 2007;Thorndyke & Yekovich, 1980). Ghosh, Moscovitch, Melo Colella, and Gilboa (2014) demonstrated that vMPFC damage, particularly to the subcallosal vMPFC, disturbs schema activation and use.…”
Section: Prior Knowledge Activation Entails Reinstatement and Instantiationmentioning
confidence: 99%
“…Theories of schema processing construe schema activation as a two-step process: (i) reinstatement of a generalized, abstracted knowledge template containing variables, such as action scripts or contextual factors, and their interrelations, and (ii) specific instantiations of a schema that contextualize schema variables in the current environment (Gilboa & Marlatte, 2017;Gilboa & Moscovitch, 2017;Barsalou, 1985;Thorndyke & Yekovich, 1980). Neurocognitive models suggest that (i) cross-regional communication between the vMPFC and posterior cortical areas mediate these processes, (ii) they influence how we process information in the environment, (iii) their influence is rapid, and (iv) their activation and maintenance is context-sensitive (Gilboa & Moscovitch, 2017;Fruhholz, Godde, Lewicki, Herzmann, & Herrmann, 2011;Hanson, Hanson, Halchenko, Matsuka, & Zaimi, 2007;Thorndyke & Yekovich, 1980). Ghosh, Moscovitch, Melo Colella, and Gilboa (2014) demonstrated that vMPFC damage, particularly to the subcallosal vMPFC, disturbs schema activation and use.…”
Section: Prior Knowledge Activation Entails Reinstatement and Instantiationmentioning
confidence: 99%
“…Such sensory ambiguous input is encoded by the brain by comparing the input with internal representations. The speed of this comparison depends on the percept and its level of ambiguity but also on the readiness of individuals to impose internal representations [1214]. At an early stage of processing, familiar interpretations are dominant.…”
Section: Introductionmentioning
confidence: 99%
“…In the taskirrelevant group, the instantiated schema did not hold contextually relevant information that could help the individual deal with the stressor. Such incongruency may have prompted the reinstatement of the dominant schema for having to give a presentation in front of a jury (Frühholz et al, 2011;van Kesteren et al, 2020), which is negatively biased for many people. Furthermore, this incongruence resulted in that these participants felt less prepared to deal with the stressor, as reflected by heightened anticipatory stress and stronger engagement of frontal emotion regulation.…”
Section: Discussionmentioning
confidence: 99%